Cultural Issue and its Influence in the Management of Global Project Teams - Lima, Nadia; Patah, Leandro Alves (Future Studies Research Journal: Trends and Strategies, 2016)
The interactions between the project manager and team members may be affected by several variables, such as culture, leadership style of the project manager, and the complexity of the developed tasks. Focused in this context, the objective of this paper is to investigate and describe how the culture issue can affect the anagement of global project teams. It is a qualitative, descriptive study conducted in a large multinational company in the automotive sector. The results of this research show that cultural issues can influence both positively and negatively the management of project global teams and the managers of these projects have to deal with several management challenges that require the adoption of certain ways of dealing with culture impacts in managing their teams to minimize potential problems in this context.